Southwest Research-Extension Center, Field Day 2001 (Kansas Agricultural Experiment Station Research Reports, 2001)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 2001; SRP877; crops; tillage; weed science; insect control